ISLAM DAN PENDIDIKAN MADRASAH DI FILIPINA - Muhamad Murtadlo (Badan Litbang dan Diklat Kementerian Agama RI, 2015)
AbstractMadrasah in some Southeast Asian countries have a unique position, besides being as a place of teaching and educating Islam, it also performs the function of formal education. This study will examine the position of madrasah in one of the Southeast Asian countries, namely the Philippines. Madrasah in the Philippines was initially considered as part of the seeding the idea of separatist Moro people who want to separate from the Philippines. This research was conducted by literature study approach, with the aim of tracing the history and treatment of the Philippines government to this kind of educational institutions. The results showed that the Philippine government has started to accommodate madrasah in their national education system.AbstrakMadrasah di beberapa negara Asia Tenggara mempunyai posisi unik, di samping sebagai tempat pengajaran dan pendidikan agama Islam lembaga ini ternyata juga menjalankan fungsi pendidikan formal. Penelitian ini ingin mengkaji posisi madrasah di salah satu negara Asia Tenggara, yaitu Filipina. Madrasah di Filipina awalnya dianggap sebagai bagian dari penyemaian ide separatisme bangsa Moro yang ingin memisahkan dari Filipina. Penelitian ini dilakukan dengan pendekatan studi kepustakaan, dengan tujuan melacak sejarah dan perlakuan pemerintah Filipina terhadap lembaga pendidikan jenis ini. Hasil penelitian menunjukkan bahwa pemerintah Filipina mulai mengakomodasi lembaga pendidikan madrasah dalam sistem pendidikan nasional mereka.